Os quadros parietais nas escolas do Sudeste brasileiro (1890-1970) - Faria, Joana Borges de (2017)
The wall chart is type of didactic material used to transmit school knowledge. It is the graphic representation on a flat surface of a determined subject matter. They are called wall charts because they are hung on the wall or within other apparatuses so that they can be viewed by all students simultaneously. Upon taking into consideration that these wall charts were widely utilized in schools across Brazil and in other occidental countries from the second half of the 19th Century until the middle of the 20th century, this research seeks to discover the history of this kind of didactic material in Brazil, focusing on how they were circulated, the individuals and companies involved in their production and distribution, their materiality, and their pedagogical functions, taking into consideration the school subjects of reference, the subject matter broached, and the visual language employed. For this purpose, the research used as source material the wall charts found in the following archives: CRE Mario Covas - Acervo da E.E. Caetano de Campos; Memorial do Colégio São Luís; Colégio Marista Glória e Centro de Memória da Educação Brasileira do Instituto Superior de Educação do Rio de Janeiro. Additional sources included the catalogues of companies that sold wall charts, mainly the French company Maison Deyrolle; manuals explaining the use of wall charts; work done by students of the Intituto de Educação do Rio de Janeiro from the 1950s and 1960s; photographs of classrooms, natural history, physics and chemistry classrooms, educational museums in schools, libraries, and dental clinics from schools in São Paulo; official documents like legislation and teaching programs for the primary and secondary schools of São Paulo and Rio de Janeiro, inventory logs as well as annual reports from directors and school inspectors; guides and visitors logs to universal expositions that occured in the second half of the 19th century; educational periodicals like Revista Pedagógica, Revista de Ensino, Revista Escolar, and Revista do Ensino do Rio Grande do Sul; and online databases related to scientific and educational heritage. The wall chart is an artefact and a visual image at the same time. For this reason, the study considers its principle theoretical references to be studies in material culture, in the material culture of schools, and in visual culture